Influence of fluid dynamic conditions on 1, 3‐propanediol production from glycerol by Shimwellia blattae: carbon flux and cell response. Issue 8 (24th February 2017) - Rodriguez, Alberto; Santos, Victoria E; Gomez, Emilio; Garcia‐Ochoa, Felix
ABSTRACT: BACKGROUND: The study of fluid dynamic conditions is essential in the development and the scaling‐up of bioprocesses. If the working volume is large, different turbulence regimes could appear during the fermentation, affecting the metabolic state of the overall culture. In anaerobic systems, increasing the stirrer speed can induce hydrodynamic stress, increasing shear stress, and its consequences can negatively affect the cell viability, reducing the yield or the productivity of the process. RESULTS: A kinetic model was employed for describing the time course of biomass growth rate and the different metabolite production rates. An increase in agitation from 100 to 500 rpm enhanced 1, 3‐propanediol (PDO) production and biomass growth rate. However, when stirrer speed was increased from 600 to 1000 rpm, the shear stress had a negative effect, decreasing the maximum PDO concentration reached and the glycerol uptake rate. Cellular response to shear stress conditions was also observed by the time course viable cells and cell images. CONCLUSIONS: The production of PDO from raw glycerol by S. blattae is favored by increasing the stirrer speed to 500 rpm. Cell viability and integrity are compromised by hydrodynamic stress under aggressive agitation conditions (>600 rpm). © 2017 Society of Chemical Industry